2020
DOI: 10.1101/2020.03.04.20031237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring diseases/traits and blood proteins causally related to expression of ACE2, the putative receptor of SARS-CoV-2: A Mendelian Randomization analysis highlights tentative relevance of diabetes-related traits

Abstract: The novel coronavirus 2019-nCoV has caused major outbreaks in many parts of the world. A better understanding of the pathophysiology of COVID-19 is urgently needed. Clinically, it is important to identify who may be susceptible to infection and identify treatments for the disease.There is good evidence that ACE2 is a receptor for 2019-nCoV, and studies also suggested that high expression of ACE2 may increase susceptibility to infection. Here we conducted a phenome-wide Mendelian randomization (MR) study to pri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 72 publications
0
20
0
4
Order By: Relevance
“…The relationship between increased risk of mortality attributable to acute severe respiratory infections in patients with diabetes mellitus has been extensively reported, particularly for the Italy [5,23,24]. Increased susceptibility for COVID-19 in patients with diabetes may be explained for several potential mechanisms including an increased lung ACE2 expression and elevated circulating levels of furin, a protease involved in viral entry to cells, and a decreased clearance of SARS-CoV-2 viral particles in subjects with diabetes and/or hypertension associated with ACE2 expression [25][26][27][28]. Impairments in immunity observed in patients with diabetes are characterized by initial delay in activation of Th1 cell-mediated immunity and late hyper-inflammatory response and are consistent with the increased risk associated with additional immunosuppression observed with our data [29].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between increased risk of mortality attributable to acute severe respiratory infections in patients with diabetes mellitus has been extensively reported, particularly for the Italy [5,23,24]. Increased susceptibility for COVID-19 in patients with diabetes may be explained for several potential mechanisms including an increased lung ACE2 expression and elevated circulating levels of furin, a protease involved in viral entry to cells, and a decreased clearance of SARS-CoV-2 viral particles in subjects with diabetes and/or hypertension associated with ACE2 expression [25][26][27][28]. Impairments in immunity observed in patients with diabetes are characterized by initial delay in activation of Th1 cell-mediated immunity and late hyper-inflammatory response and are consistent with the increased risk associated with additional immunosuppression observed with our data [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that smokers, especially males, may be more susceptible to infection with COVID-19. With regard to the association between cancer and susceptibility to infection with COVID-19, it has been reported in recent studies that breast, colorectal, and lung cancer may be associated with an increased expression of ACE2 (8,10). Zheng et al (16) reported that 8 (1%) of 1,590 COVID-19 cases had a history of cancer, which seems to be higher than the incidence of cancer in the overall Chinese population ([0.29%] per 100,000 people).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al (5) reported that older age (odds ratio [OR] = 8.546, 95% confidence interval [CI] = 1.628-44.864, p = 0.011) and smoking (OR = 14.285, 95% CI = 1.577-25.000, p = 0.018) are risk factors for the progression of COVID-19. Rao et al (8) showed that over 25% of patients with COVID-19 have a history of hypertension (12.9%) and diabetes (5.4%). However, it is still unclear whether the above factors, or perhaps even other factors, are associated with susceptibility to COVID- 19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACE2 gene expression studies of kidney tissue to date have been inconclusive concerning regulation in kidney disease [50][51][52][53] . A strength of our study is the definition of the ACE2 expression to the cellular context of PTEC in distinct infectious and non-infectious kidney diseases.…”
Section: Discussionmentioning
confidence: 99%